Microfinance institutions in Poland: Towards preventing social and financial exclusion - Joanna Fila (Economic and Environmental Studies (E&ES), 2018)
The idea of microfinance is well known now around the world. It can develop both in poor countries and in highly developed ones. Microfinance aims to reach two basic goals: to stimulate the borrowers in order to trigger activities that would generate income and to reach social objectives which would make social integration possible and thus enable individuals to integrate financially. The microfinance market in Europe differs from those in poorer countries as regards the level and range of support, the form of microcredit and other microfinance products. It also faces certain challenges. The market of financial services comprises various entities which offer a wide range of products to customers. The objective of microfinance institutions is to provide financial services, such as microcredit/microloan to the persons who face difficulties entering the job market or are socially and financially excluded. Having access to finance is an important determinant for the development of enterprises. The aim of this paper is to explore the issue of social and financial exclusion in the context of microfinance institutions in Poland. Social and financial exclusion regards poorer individuals and micro enterprises that do not have easy access to mainstream banking sector. Microfinance is supposed to bridge this financial gap. The paper discusses the opportunities and challenges that are faced by the microfinance sector in Poland.
Keywords: G21; G23; 330; microfinance institutions; microcredit/microloan; social and financial exclusion